Perioperative Complications in Patients with Rheumatoid Arthritis Following Primary Total Knee Arthroplasty: An Analysis of 102,898 Patients - Vakharia, Ajit M.; Cohen-Levy, Wayne B.; Vakharia, Rushabh M.; Sodhi, Nipun; Mont, Michael A.; Roche, Martin W. (The Journal of Knee Surgery, 2019)
There are conflicting results regarding the impact of rheumatoid arthritis (RA) on total knee arthroplasty (TKA) outcomes. Therefore, the purpose of this study was to compare outcomes of patients with and without RA undergoing primary TKA. Specifically, we assessed (1) 90-day medical complications, (2) 90-day readmission rates, (3) short-term implant-related complications, (4) 1-year mortality, and (5) total global 90-day episode-of-care costs. The authors of the study hypothesize that RA would increase the rate of medical- and implant-related complications, readmission rates, and costs. A retrospective level of evidence III study was conducted using the Medicare standard analytical files from the PearlDiver database. Patients were queried using the International Classification of Disease, ninth revision codes. Patients with RA were randomly matched 1:1 to controls according to age, gender, and Charlson's comorbidity index. Two mutually exclusive cohorts were formed. Medical- and implant-related complications, readmission rates, and costs were analyzed and compared between the cohorts. Statistical analysis using logistic regression was performed calculating odds ratios (OR), 95% confidence intervals (95% CI), and their respective p-values. The query returned 102,898 patients with (n = 51,449) and without (n = 51,449) RA undergoing primary TKA within the Medicare database from 2005 to 2014. Patients with RA had greater odds of medical complications (OR: 2.08, 95% CI: 1.98–2.20, p < 0.001), implant complications (OR: 1.30, 95% CI: 1.24–1.36, p < 0.001), 1-year mortality (OR: 1.35, 95% CI: 0.68–2.70, p = 0.39), total 90-day episode-of-care costs ($16,605 vs. 15,716.53; p < 0.001), and 90-day readmission rates were similar between cohorts (OR: 1.08, 95% CI: 1.05–1.12, p < 0.001). RA increases postoperative complications and costs following primary TKA within Medicare patients. Comprehensive preoperative optimization for patients with a diagnosis of RA may mitigate perioperative complications, thus improving patient outcomes, and ultimately reducing episode-of-care costs.
Keywords: total knee arthroplasty; rheumatoid arthritis; Medicare; outcomes